The Influence of Different Amaranth Leaf Meal Inclusion Levels on Performance, Blood Profiles, and Gut Organ Characteristics of Ross 308 Broiler Chickens - Manyelo, Tlou Grace; Sebola, Nthabiseng Amenda; Ng'ambi, Jones Wilfred; Weeks, William; Mabelebele, Monnye (Frontiers in Veterinary Science, 2022)
The aim of this study was to determine the effect of varying inclusion levels of amaranth leaf meal inclusion level on the performance, blood profiles and gut organ characteristics of Ross 308 broiler chickens. A total of 200, day-old, Ross 308 broiler chicks were randomly allocated to five dietary treatments in a complete randomised design, with each group having four replicates with ten chicks. Amaranth leaf meal (ALM) inclusion levels used in this study were 0, 5, 10, 15 and 20%, body weight and feed intake were measured on a weekly basis to calculate the feed conversion ratio. Gut organ weights, lengths, organ pH and blood profiles were measured, and the general linear model of statistical analysis software was used to analyse collected data. ALM had no effect (p>0.05) on feed intake, body weight or the feed conversion ratio of Ross 308 broiler chickens aged one to 42 days, respectively. Furthermore, ALM inclusion levels had no effect (p>0.05) on dry matter, (DM), crude protein (CP), or gross energy (GE) digestibility of Ross 308 broiler chickens. Ross 308 broiler chickens which were fed with 5 and 15% ALM inclusion levels, had higher (p<0.05) overall blood profiles than those fed with diets containing 0, 10 and 20%. ALM inclusion of 5% had higher (p<0.05) essential and non-essential amino acid digestibility in Ross 308 broiler chickens. ALM inclusion levels had no effect (p>0.05) on gut organ lengths or weights of Ross 308 broiler chickens aged 21 and 42 days. In conclusion, 5, 15 and 15% ALM inclusion levels can be included in broiler chickens without having any adverse effect on the chickens’ performance. This indicates that ALM can be added to broiler diets at any inclusion rate without negatively affecting their performance.